The Modern Vision of Knowledge and Its Impact in the Art: Transparency - Aizpún de Bobadilla, Teresa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2018)
The metaphor of transparency has always embodied the human longing for perfection. Transparency or that which hides nothing, what allows us to see through itself not leaving any space to mystery, is as a matter of fact the symbol of perfect knowledge. This very idea had an incredible influence on art, but transparency is a wonderfully broad concept and its meaning is not univocal and much less in the first decades of the 20th century, when not only does it become the symbol of perfection in knowledge but also the symbol of all perfection: of the new man and the new society.